CROSS-FUNCTIONAL INTERACTION AND COMMUNICATIONS IN CRISIS CONDITIONS (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Abstract. The article discusses the issue of using cross-functional teams as a tool for quick response to changes in crisis conditions. Special attention is paid to the study of cross-functional interaction and communications in crisis conditions. It is well-founded that in a crisis, cross-functional teams are particularly effective, as they can ensure quick and effective interaction between different functional areas of the company.The purpose of the article is to study cross-functional interaction and communications in crisis conditions and their impact on the effectiveness of exiting it. The task of the research is to establish the relationship between an effective approach to communications in crisis conditions and the organizational work of a cross-functional team, to highlight the advantages of cross-functional cooperation, to analyze the difficulties and real problems of the current interaction of cross-functional teams, to form directions for improving the construction of communications and information flows in crisis conditions.Based on the research, it was determined that communication is a key element of interaction in a cross-functional team. Team members must regularly communicate with each other, share ideas and information to ensure that tasks are completed effectively. It was determined that the nature of the communication system of any organization largely depends on the type of structural systems used to build the management system. The basis of the cross-functional management structure is the organization of work groups. It has been proven that each crisis situation has its own differences and unique components that are difficult to calculate in advance. To form a communication response and develop a plan, it is important to analyze the crisis situation and understand its anatomy. Two main groups of crises are distinguished – operational and reputational, and the differences in communicative response are analyzed, depending on the type and level of the crisis.A cross-functional team is a group of people with different skills and experiences who work together to achieve a common goal and can help ensure more efficient use of resources and reduce the time needed to make decisions. It has been proven that cross-functional interaction causes a synergistic effect, which is different from the total work of individual structural divisions of the enterprise. Such teams can provide greater flexibility and speed of response to changes in crisis conditions, it is important that each team member understands his responsibilities and contribution to the common cause.
Keywords: cross-functional interaction, communication, cross-functional team, crisis, crisis situation